Thermal performance predictions for an HFE-7000 direct flow boiling cooled battery thermal management system for electric vehicles - Wang, Yan-Feng; Wu, Jiang-Tao (Energy conversion and management, 2020)
•A novel refrigerant-based battery thermal management system is proposed.•Temperature distributions and boiling characteristics are predicted.•The maximum temperature is inversely correlated with refrigerant inlet velocity.•Temperature uniformity is predominantly affected by nucleate boiling heat transfer. In this paper, a novel battery thermal management system (BTMS) using the dielectric, non-flammable HFE-7000 refrigerant is proposed for electric vehicles (EVs). Its thermal performance is studied both numerically and experimentally. The refrigerant flows and boils on the battery wall surfaces, which lowers the thermal contact resistance as well as enhances the heat transfer process. Therefore, the thermal performance of the battery module is improved. The results indicate that forced convection heat transfer of the liquid refrigerant is dominating in the control of the temperature rise in the battery module. The maximum battery temperature drops to 35.10°C at 0.3ms-1 inlet velocity and a 5C discharge rate. In contrast, the temperature uniformity between individual battery cells primarily depends on the nucleate boiling heat absorption and local perturbation of the two-phase turbulent flow. A temperature difference of no more than 3.71°C can be observed at 5C discharge rate and 0.1ms- 1. In addition, good agreement was found between the numerical results and experimental data.